Comparison between Standing and Supine Lateral Radiographs in Low Grade Spondylolisthesis - Dhakal, Gaurav Raj; Biswas, A; Rathinavelu, S; Patel, D Kumar K; Basu, S (Journal of Manmohan Memorial Institute of Health Sciences, 2015)
To analyze the differences between standing and supine plain film lateral radiographs of the lumbosacral region in low grade (grade I/II) spondylolisthesis using the Picture Archiving and Communication System (PACS) software. Demonstrable difference might be a parameter of instability which might be useful in planning surgical treatment when it is too painful for patients to undergo flexion/extension Xrays.Radiographs of 23 patients with low grade spondylolisthesis were analyzed for percentage slip, lumbar lordosis, disc height, sacral inclination and slip angle. These standing and supine lateral radiographs were taken at the same distance with the same magnification. Measurements obtained were statistically analyzed with the SPSS software using the student t test for statistical significance (p